Meningkatkan Aktivitas dan Hasil Belajar Mata Pelajaran Pendidikan Kewarganegaraan Melalui Penerapan Model Pembelajaran Berbasis Masalah Pada Siswa Semester II kelas VI SDN 2 Seraya - I Wayan Sudiarta (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2019)
This research is a classroom action research with 22 research subjects. The purpose of this study is to improve student learning outcomes problem-based learning models in PKN learning. The formulation of the problem is whether the application of the demonstration method in PKN subjects can improve the learning outcomes of class VI students in Semester 2 of SD Negeri 2 Seraya. The purpose of this study was to determine how much the increase in PKN learning outcomes of class VI students of SD Negeri 2 Seraya while applying the demonstration method on PKN learning. This study was conducted in class VI SD Negeri 2 Seraya in the 2016/2017 school year with 11 research subjects. Data collection uses the method of observation and student learning outcomes tests. The results of the research obtained in this study are]) The application of problem-based learning models can improve learning activities of PKN subjects in students of Semester II Class VI SD Negeri 2 Seraya with an average acquisition of 52% in cycle I to 78% in cycle II and achievement completeness of 9% in the first cycle to 91% in the H cycle which is above the standard set; 2) Application of problem-based learning models can improve learning outcomes of subjects [PA in semster II Class VI students SD Negeri 2 Seraya. While with absorption from 64% in cycles] to 77 ° o in cycles]] and learning completeness by 55% in cycle I to 91% in cycle II which is above the standard set.